A Photoaging Intervention Delivered to Adolescents in Secondary Schools: A Feasibility Study. (19th July 2022) - McNoe, Bronwen M.; Morgaine, Kate C.; Reeder, Anthony I.; Iosua, Ella
Abstract : Excessive exposure to ultraviolet radiation during adolescence can have a lasting effect on long-term skin cancer risk. Skin cancer prevention interventions for adolescents have been less commonly investigated than those for children and adults. The study objectives were to develop and evaluate the feasibility of a secondary school-based appearance focused intervention, including the development and testing of protocols and instruments, as a resource module that could be efficiently integrated into the secondary school science curriculum. This longitudinal study was conducted with a convenience sample of 38 13–14 year-old students attending one New Zealand (NZ) urban secondary school. The recruitment rate was excellent with only one student not participating because of parental concern. In terms of the implementation practicality, the intervention, as it stands, was extremely resource intensive, involving four research staff to deliver. This will not work if delivered in a classroom setting by a single teacher. However, the intervention was well received by students, so it shows promise if a less resource intensive version could be produced. The acceptability of the intervention with the students was good with the majority (61%) having no suggestions for improvements. Suggested improvements were minor and could be easily addressed.